1987
DOI: 10.1007/bf00230146
|View full text |Cite
|
Sign up to set email alerts
|

A novel stimulator of protein phosphorylation in Neurospora crassa

Abstract: An endogenous thermostable activator of Protein kinase III (PKIII) was purified from 100,000 X g supernatants of Neurospora crassa mycelial extracts. This 38,000 dalton polypeptide, clearly separable from calmodulin on P-60 gel filtration, specifically stimulated N. crassa PKIII activity on casein or phosvitin "in vitro" phosphorylation. The factor was only present in the initial growth phase of the fungus. The mechanism of PKIII activation and its possible regulatory role are discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

1991
1991
2016
2016

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 8 publications
1
6
0
Order By: Relevance
“…They found that purified PK-III was inhibited by fenpiclonil and fludioxonil (Pillonel and Meyer, 1997). Although the concentration of phenylpyrroles required for PK-III inhibition was found similar to that of rat PKC-inhibition, N. crassa PK-III does not seem to be neither a Ca 2+ /calmodulin nor a cAMP regulated protein kinase (Judewicz et al, 1981; Ulloa et al, 1987). To some extend the inhibition of PK-III correlated with growth inhibition by fenpiclonil, but less by fludioxonil, raising the question if phenylpyrroles, especially fenpiclonil, directly inhibit PK-III activity.…”
Section: Effect Of Phenylpyrroles On Target Fungi – Mode Of Actionmentioning
confidence: 85%
“…They found that purified PK-III was inhibited by fenpiclonil and fludioxonil (Pillonel and Meyer, 1997). Although the concentration of phenylpyrroles required for PK-III inhibition was found similar to that of rat PKC-inhibition, N. crassa PK-III does not seem to be neither a Ca 2+ /calmodulin nor a cAMP regulated protein kinase (Judewicz et al, 1981; Ulloa et al, 1987). To some extend the inhibition of PK-III correlated with growth inhibition by fenpiclonil, but less by fludioxonil, raising the question if phenylpyrroles, especially fenpiclonil, directly inhibit PK-III activity.…”
Section: Effect Of Phenylpyrroles On Target Fungi – Mode Of Actionmentioning
confidence: 85%
“…When acid substrates such as phosvitin or casein were used as acceptors, the reaction was stopped with 10% TCA according to Ulloa et al (1987). The Ko.5 for Ca2+ was determined in the presence of EGTA-Ca2+ buffers according to Bartfai (1979).…”
Section: Protein Kinase Activity Assaysmentioning
confidence: 99%
“…A wild type Neurospora crassa strain (St. Lawrence 74) was grown in Vogel's minimal medium supplemented with 2% (w/v) sucrose and 2.5tzg/ml dbiotin as described [4]. Cultures were shaken (100 oscillations/min) at 30°C in 1000 ml Erlenmeyer flasks containing 200 ml medium in a rotatory air incubator.…”
Section: Culturesmentioning
confidence: 99%
“…A second one is dependent on Ca 2+ and calmodulin [3]. A third type of mechanism involves a protein kinase, specific for phosvitin, which is activated by an endogenous thermostable peptide [4]. Recently, a fourth type of regulatory mechanism was described involving a Ca 2+phospholipid dependent protein kinase C [5].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation